Russia’s War Against Ukraine: A Geopolitical Turning Point for EU Enlargement? - Oliver Schwarz (European Journal of Risk Regulation)
This article explores whether Russia’s war against Ukraine represents a geopolitical turning point for the European Union’s enlargement policy. By applying the concepts of historical institutionalism and turning points, the study examines a potential shift in EU priorities from normative to geopolitical considerations. Through a bibliometric analysis of academic literature and a quantitative analysis of progress reports from 2013 to 2023, the findings reveal that while the EU has increasingly incorporated geopolitical factors into its enlargement strategy, these changes do not yet constitute a definitive turning point.